Impact of students’ feedback on their engagement towards online classes during COVID-19 pandemic - Rudnák, Ildikó; Hamza, Khadija Aya; Alshaabani, Ayman; Garamvölgyi, Judit (International Journal of Evaluation and Research in Education (IJERE), 2024)
With the emerge of COVID-19 pandemic in Hungary, Hungarian universities have decided to opt for online teaching methods even for foreign language courses. This sudden change has required a better understanding of students’ behaviors in classes also to view the importance of their feedback to enhance teaching quality and teachers’ effectiveness. The purpose of our study was to focus on students’ feedback and its impact on their engagement in the context of online classes, by considering the mediating role of teaching effectiveness in that relationship. Structural equation modelling was used to examine our primary data, which has been collected from a distributed online questionnaire dedicated to 222 students enrolled in Hungarian language courses at MATE University. The findings reveal that students’ feedback has a direct, significant, and positive effect on students’ engagement in online classes and teaching effectiveness, which itself plays a mediating role in that relationship.